2002
DOI: 10.1086/344729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism ofClostridium difficileToxin A–Induced Apoptosis in T84 Cells

Abstract: This study is an investigation into the mechanism of Clostridium difficile toxin A-induced apoptosis in human intestinal epithelial cells. Toxin A induced apoptosis of T84 cells in a dose- and time-dependent fashion. Toxin A-induced apoptosis was completely inhibited by blocking toxin enzymatic activity on Rho GTPases with uridine 5'-diphosphate-2',3'-dialdehyde by a nonspecific caspase inhibitor and was partially inhibited by caspase-1, -3, -6, -8, and -9 inhibitors. Caspases 3, 6, 8, and 9 and Bid activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
131
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(145 citation statements)
references
References 57 publications
10
131
1
Order By: Relevance
“…Both pathways culminate in the activation of downstream executioner caspase-3. The activation of caspase-3 results in a series of events, such as cleavage of cytoskeleton proteins, activation of nucleases, and subsequent DNA fragmentation [30]. The results of the present study demonstrate that VacA induces cytochrome c release from the mitochondria into the cytoplasm in eosinophils.…”
Section: Discussionsupporting
confidence: 55%
“…Both pathways culminate in the activation of downstream executioner caspase-3. The activation of caspase-3 results in a series of events, such as cleavage of cytoskeleton proteins, activation of nucleases, and subsequent DNA fragmentation [30]. The results of the present study demonstrate that VacA induces cytochrome c release from the mitochondria into the cytoplasm in eosinophils.…”
Section: Discussionsupporting
confidence: 55%
“…The GTD has been shown to target and inactivate a number of Rho-family GTPases (19,20). This inactivation has been linked to a cell rounding or cytopathic effect (CPE) (21)(22)(23)(24) and to an apoptotic cytotoxic effect (25)(26)(27)(28)(29)(30)(31)(32)(33). In tissue culture models, the apoptotic effects of TcdA and TcdB occur at toxin concentrations of picomolar or lower and are evident at 24 to 48 h postintoxication (26,28,29,(34)(35)(36).…”
mentioning
confidence: 99%
“…The activation of caspase-9, cytochrome C release, and changes in mitochondrial membrane potential indicate TxA stimulates the intrinsic pathway of apoptosis. The implication of the extrinsic pathway was also confirmed by the activation of caspase-8 and BID (Brito et al, 2002). The findings obtained by Brito et al (2002) were subsequently confirmed by Carneiro et al (2006) under both in vitro and in vivo conditions.…”
Section: Clostridium Difficile Toxin Amentioning
confidence: 68%
“…Apoptosis modulated by toxin A (TxA) was investigated in a study by Brito et al (2002) which revealed that TxA is capable of inducing cell death in T-84 cells. The involvement of caspases in the apoptosis mediated by TxA was verified with the use of fluorescent substrates specific to caspases-3, -6, -8, and -9.…”
Section: Clostridium Difficile Toxin Amentioning
confidence: 99%